2015
DOI: 10.4103/0253-7176.150823
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Care: A Study of Patients Hospitalized for Treatment of Psychotic Illness

Abstract: Background:Combination of ill health and poverty poses special challenges to health care providers. Mental illness and costs are linked in terms of long-term treatment and lost productivity, and it affects social development. The purpose of the present study is to assess the economic burden of poor families when a family member needs hospitalization due to psychosis.Materials and Methods:The information was gathered from caregivers of 100 psychotic inpatients of Medical College Hospital of Kerala during a peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The finding is similar to the study by Rejani et al . [ 22 ] In our tertiary care hospital setup, most of the investigations and drugs are available in hospital pharmacy and are free of cost. However, after discussion with psychiatrists, it was found that some drugs such as escitalopram, olanzapine, and clonazepam are sometimes not available in hospital pharmacy and patients have to purchase these drugs from the outside.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is similar to the study by Rejani et al . [ 22 ] In our tertiary care hospital setup, most of the investigations and drugs are available in hospital pharmacy and are free of cost. However, after discussion with psychiatrists, it was found that some drugs such as escitalopram, olanzapine, and clonazepam are sometimes not available in hospital pharmacy and patients have to purchase these drugs from the outside.…”
Section: Discussionmentioning
confidence: 99%
“…Though 76% received mediations from hospital, some drugs had to be purchased for better management. Even 45% of the caregivers had to cut back work due resulting in significant loss of financial support for the patients (Rejani, Sumesh, & Shaji, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if the ADR report is classified as insufficiently documented or fails to fulfill the approved and specific criteria, it will be excluded from further pharmacovigilance assessment. [ 8 ] The quality of ADRs reported problem was the focus of attention and concern of the relevant authorities involved in the pharmacovigilance activities. Therefore, it is essential to encourage health-care providers as well as the patients to submit a complete ADR report form and check the quality of the form in its initial preparation stages.…”
Section: Introductionmentioning
confidence: 99%